Book review: The Routledge Handbook of Second Language Acquisition and Writing - Chen, Meiling; Zheng, Yao (Journal of Writing Research, 2022)
The Routledge Handbook of Second Language Acquisition and Writing is a collection of research papers edited by Rosa M. Manchón and Charlene Polio. They aim to create a compendium that serves to contextualize and synthesize the development and research practices of the connection between second language (L2) writing and second language acquisition (SLA). The chapters of the collection feature theoretical perspectives and current empirical development on how and why L2 writing can be a meaningful site for language learning. Three reasons are formulated to articulate the significance of the volume concerning SLA-informed L2 writing studies: (1) research outcomes in this research domain are theoretically and empirically fruitful; (2) the theoretical contributions to the SLA knowledge are newly achieved; (3) L2 writing plays an indispensable role in instructed second language acquisition (ISLA) settings. By taking into account the socially situated nature of L2 writing teaching and learning, Manchón and Cerezo (2018) highlighted the substantial value of integrating L2 writing with SLA theories and research for both boosting the L2 learning process and advancing present and prospective SLA research agendas. Such an academic viewpoint appears to be predominant and invaluable in this collection with its theoretical advancements and practical insights contributed by authors from diverse educational settings.